2012
DOI: 10.1111/j.1365-3059.2012.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of phytosanitary controls in preventing the entry of Colletotrichum acutatum in the UK strawberry sector

Abstract: Phytosanitary legislation is widely thought to be the most effective means of limiting the entry of alien pathogens without hindering trade. However, there is increasing evidence of limitations and weaknesses in phytosanitary systems worldwide. One such case is the entry and establishment of Colletotrichum acutatum in the UK in the 1980s. To investigate this further, data sets of disease incidence gathered by the authorities responsible for plant health between 1984 and 2008 were analysed to determine how and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Latently infected planting material can be an important source for C. acutatum inoculum in the field (Calleja et al, 2013). In the present study, a standard protocol was developed for molecular detection of the latent presence of C. acutatum in the old petioles and runners of planting material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latently infected planting material can be an important source for C. acutatum inoculum in the field (Calleja et al, 2013). In the present study, a standard protocol was developed for molecular detection of the latent presence of C. acutatum in the old petioles and runners of planting material.…”
Section: Discussionmentioning
confidence: 99%
“…Planting material that is latently infected with C. acutatum is believed to be the main inoculum source (Sreenivasaprasad & Talhinhas, 2005;Smith, 2008;Calleja et al, 2013). Colletotrichum acutatum has been detected on strawberry planting material in Switzerland (Bosshard, 1997), Finland (Parikka & Lemmetty, 2004) and Belgium (Debode et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in the UK (Calleja et al., ) found for a specific pest ( Colletotrichum acutatum ) that border inspections intercepted about 50% of infested strawberry plants using data of traceable outbreaks on farms. The FVO () carried out an audit in 2011 in a Member State and reported that the inspections cannot in all cases be considered to be based on representative samples.…”
Section: Appendix a – Formal Model And Parameters Estimatesmentioning
confidence: 99%
“…In Europe, C. acutatum is the most prevalent species causing anthracnose, whereas C. gloeosporioides is found only occasionally, and C. fragariae has not yet been observed (Denoyes and Baudry, 1995;Garrido et al, 2008). In UK, the first incidence of anthracnose disease in strawberries caused by C. acutatum was attributed to the importation of infected strawberry runners from the USA (Calleja et al, 2012). These fungal species affects fruit quality and causes significant pre-and post-harvest fruit losses, especially during wet weather (Prusky and Plumbey, 1992;Prusky, 1996;Arauz, 2000;Chrys, 2006).…”
mentioning
confidence: 99%